A MODEL ON THE STRUCTURE AND ORGANIZATION OF THE POLYTENE CHROMOSOME BASED ON THE STUDY ON CHIRONOMUS STRIATIPENNIS KIEFFER (DIPTERA: CHIRONOMIDAE) - SWAPNA BHADURI; SUDHANGSU KUMAR GHOSAL (The Bioscan, 2013)
A study on the polytene chromosomes obtained from the salivary gland cells of Chironomus striatipennis Kieffer indicated that a polytene chromosome is not a typical ribbon like body formed of a number of thread like chromatin elements aligned side by side having condensed chromatin thread at locations forming bands, simple linear threads of chromatin as interbands and highly extended chromatin threads forming Balbiani rings and puffs at places as conventionally thought of, instead a chromosome appears to be a cylindrical body with thin and thick circular bands as elevated regional differentiation of the chromatin threads having interbands in between as depressed regions over a chromosome. The polytene chromosomes prepared from the Chironomid larvae showed the characteristic configurations to support the organization of polytene chromosomes as conjectured. The variable dimensions of bands appeared due to variable amount of condensed chromatin material and intervening interbands also varied in their magnitude of extension. Besides some regions of excessive constriction also appeared as waists along a chromosome arm and such differentiation could be possible due to presence of some quasifluid substance making the core of the cylindrical chromosome. The multiple chromatin threads in the polytene chromosome appeared to be arranged on the surface line of the long chromosome with coiled or kinky orientation of the thread at identical locations in all the chromatin threads. The chromatin threads were so arranged that the surface of the chromosome appeared smooth laterally except some swelled protrusions at places. The swelled protrusions were the bands and the depressed regions between them were the interbands. The inner core of the cylindrical chromosome appeared to be filled up with a material of quasi-fluid consistency.